Mitrastemonaceae a new record family for the Philippines - Amoroso, Victor B.; Mendez, Noe P.; Lagunday, Noel E. (2018)
Mitrastemonaceae is represented by a sole genus ? Mitrastemon ? with only two known species worldwide, which parasitize on roots of many trees. This paper reports the discovery of Mitrastemon yamamotoi from Mt. Malambo, Mindanao, Philippines. Mitrastemonaceae is revealed to be a new family record for the Philippines. Added to its taxonomic description, its habitat characterization, phenology, conservation status, and implications are also discussed. (Author's abstract)